Development of Spectrophotometric Method for Aluminium Detection - Wan Khalid, Wan Elina Faradilla; Samsudin, Siti Hamizah; Raja Othman, Raja Mohamad Shafiq (2020)
In this study, a spectrophotometry method for detection of Al 3+ ion was developed using Alizarin Red S (ARS). ARS in the presence of Al 3+ ion form brown complex solution. Al ARS complex formation was characterized by using UV-Vis spectrophotometer (UV-Vis). The developed method showed a linear response in the range of 1 ppm to 10 ppm with an isosbestic point of 436 nm. Moreover, photostability study indicates that ARS exhibited a stable reading for a duration of 6 hours. This method displayed high selectivity towards Al 3+ ion concentration with no interferences from Pb 2+ , Fe 2+ , Cu 2+ and Zn 2+ ions. The ARS reagent was then immobilized in alginate to form film. Analysis using FTIR spectrophotometer shows that the presence of IR peak for ARS-alginate at 1107.44 cm -1 , 1474.09 cm -1 , 1637.77 cm and 3405.76 cm -1 .